Clinical, Immunological and Inflammatory Characteristics among Mexican Children with Different Subtypes of Juvenile Idiopathic Arthritis: Exploring the Correlation between Anti-Cyclic Citrullinated Peptide (anti-CCP) and Rheumatoid Factor (RF) - Hayde Guadalupe Hernández-Huirache; Dagoberto Armenta-Medina; Edel Rafael Rodea-Montero (MDPI AG, 2024)
Introduction: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood, affecting one to four of every 1000 children worldwide. It is characterized by joint inflammation lasting more than six weeks in children under 16 years. The aim of this study was to estimate the frequency of JIA subtypes in the Mexican patient population; compare clinical, immunological and inflammation markers by JIA subtype; and examine the correlation between these variables. Methods: We conducted a cross-sectional study of 50 patients with JIA (2-15 years). We estimated the frequency of each JIA subtype, assessed and compared the immunological characteristics (RF, ANA and anti-CCP) by JIA subtype at the time of diagnosis using Kruskal-Wallis or chi-square tests, and calculated Spearman correlation coefficients between the assessments. Results: Our analysis included 50 patients, 29 (58%) girls and 21 (42%) boys, aged at the time of diagnosis 10.56  ±  3.99 years. The frequencies of JIA subtypes were RF-seropositive polyarthritis (34%), RF-seronegative polyarthritis (28%), systemic arthritis (16%), oligoarthritis (14%) and arthritis-related enthesitis (8%). We found a significant association between sex and JIA subtype (p = 0.014). There was a significant difference in anti-CCP levels by JIA subtype (p < 0.001). We also detected positive correlations between RF and anti-CCP (r = 0.63, p < 0.001) and between age and anti-CCP (r = 0.29, p = 0.041). Conclusions: Our study suggests that the frequency of the polyarticular subtypes of JIA is higher in Mexican children compared to other populations. Our findings highlight the importance of considering the presence of anti-CCP and RF as important criteria when deciding on treatment for JIA patients as elevated levels of these antibodies may indicate early forms of adult rheumatoid arthritis.